Analysis of factors affecting regional financial independence in primary leading sector districts - Latipah, Siti Lailatul; Hady Sutjipto; Ginanjar, Rah Adi Fahmi; Setyadi, Sugeng; Didu, Saharuddin (Journal of Entrepreneurial Economics, 2025)
Background: Regional autonomy has been implemented for more than two decades, but local governments can still not manage their local finances independently. Problems that occur in the implementation of regional autonomy can occur from within and outside the country. Domestic conditions indicate that people want openness and independence, while foreign conditions indicate that the increasing progress of globalization demands the competitiveness of each country, including the competitiveness of local governments. Methods: This study uses panel data consisting of time series data from 2018 - 2022 and cross-section data on 140 districts in Indonesia that have primary leading sectors. The analysis method is the Generalized Method of Moments (GMM) method with the System Generalized Method of Moments approach to address endogeneity problems and dynamic economic correlations. Findings: The results of this study indicate that the primary output variable and tax ratio have a positive and significant effect on regional financial independence. In contrast, natural resource revenue-sharing funds and general allocation funds have a negative and significant effect. Meanwhile, the special allocation fund variable does not affect regional financial independence. Conclusion: This study concludes that enhancing primary output and optimizing tax ratios are crucial for improving regional financial independence. However, reliance on revenue-sharing funds and general allocation funds can hinder financial autonomy. Policy implications suggest the need for local governments to strengthen their economic base and reduce dependency on central government transfers to achieve greater fiscal independence. Novelty/Originality of this Article: This study provides a novel approach to analyzing regional financial independence by utilizing the System Generalized Method of Moments (GMM) to address dynamic economic correlations and endogeneity issues.